The Debt-Growth Nexus in Poor Countries: A Reassessment - Andrea F. Presbitero (Economics: The Open-Access, Open-Assessment E-Journal, 2008)
The paper investigates the relationship between external debt and economic growth, focusing on the role played by the policy and institutional framework. Results for a panel of 114 developing countries show that the debt-growth nexus depends on institutions and policies. The Debt-Laffer curve looses statistical significance once institutional quality is controlled for and debt overhang seems to be at work exclusively in countries with sound institutions. On the contrary, external debt proves to be irrelevant for countries with weak institutions. A policy implication is that efficient debt relief policies should be tailored to country-specific characteristics and conditional to a certain level of institutional quality.
Keywords: F34; H63; O11; C33; 330; External debt; HIPC; debt relief; economic growth; Auslandsverschuldung; Wirtschaftswachstum; Schuldenerlass; HIPC (Heavily Indebted Poor Countries); Schätzung; Entwicklungsländer